Hubungan Caring Perawat Terhadap Tingkat Kepuasan Pasien Di Ruang Rawat Inap 1 Rumah Sakit Umum Haji Surabaya - Siti Aisyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: Caring for nurses is a caring attitude that makes it easier for patients to achieve improved health and recovery. Whether or not a patient is satisfied in assessing the quality of nursing services is very dependent on how a nurse applies caring tips when providing nursing services. Purpose: To describe the relationship between nurse caring and the level of patient satisfaction in inpatient room 1 of the Haji General Hospital, Surabaya. Methods: Quantitative research method by applying correlational method with Cross Sectional approach. The sample in this study was 30 patients who were in the inpatient room 1 RSU Haji Surabaya. Sampling using Non Probability Sampling with Simple Random Sampling sampling technique. The research instrument used a nurse caring questionnaire and the level of patient satisfaction. The research instrument used a nurse caring questionnaire and the level of patient satisfaction. Analysis of the data using the Chi-Square test with the help of SPSS 25. Results: The results of the analysis show that there is a significant relationship between nurse caring and the level of patient satisfaction in the inpatient room 1 Rsu Haji Surabaya (ρ value= 0.01 <0.05) with a correlation value (0.598) then H0 is rejected so that Ha is accepted so there is a strong relationship and a positive relationship, the better the nurse's caring, the better the level of patient satisfaction, namely the respondent has the caring nature of the nurse 28 respondents (93%) and as many as 25 respondents (83%) have a good level of patient satisfaction. Conclusion: There is a relationship between the caring of nurses on the level of patient satisfaction in the inpatient room 1 of the Surabaya Haji General Hospital. Therefore, caring for nurses is very important in improving the quality of service in nursing, so the caring behavior of nurses needs to be improved. One way to improve caring behavior is to do in-house training. Innovation in house training is hard skill and soft skill training.Keywords: Caring Nurses, and Patient Satisfaction Level.